EFFECT OF CHLORIDE IONS ON THE PASSIVE LAYER FOR THREE AL-ALLOYS AT PH=9 - Hikmat, Naema A; Farhan, Ahlam M; Majed, Rana A (Al-Nahrain Journal of Science, 2018)
This work involves the study of the effect of chloride ion on the passive layer which is formed on the surface of three aluminium alloys (Al-Cu-Mg), (Al-Mg), and (Al-Zn). The concentrations of chloride ion used were (1x10-3, 1x10-2, 0.1 mol.dm-3). The study was performed in 1x10-5 mol.dm-3 NaOH solution which was corresponded to pH value of (9). The data of polarization behaviour were calculated by Tafel extrapolation method and the comparison of this data in the absence and presence of chloride ions were discussed.